INDONESIA NATIONALISMâ€™S CHALLENGE IN THE GLOBALIZATION ERA - Supardan, Dadang (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
We are still reminding that the long-term multidimensional crisis, the peak moment was in 1997-2000, was the worst experience in term of politic, economy, and law crisis after the Indonesia independence.The crisis may refer to a state-nation in turbulence (chaos) which many observers called as â€œA Country in Despairâ€, a country that is not only experiencing a disaster but also drowned in a deep despair. Indonesiaâ€™s multidimensional crisis had opened all the â€œmasksâ€, to its most hidden parts.This multidimensional crisis- in despair, emotionally, and sinically- had showed Indonesia as "a heap of delusions", no more nationalism, heroism, justice, unity, honesty, or proud. In conclusion, the old institutions survived with no dignityÂ This article focuses on Indonesia Nationalismâ€™s Challenge In the Globalization Era.We are still reminding that the long term multidimensional crisis, the peak moment was in 1997-2000, was the worst experience in term of politic, economy, and law crisis after the Indonesia independence.Crisis may refer to a state-nation in turbulence (chaos) which many observer called as â€œA Country in Despairâ€, a country that is not only experiencing disaster, but also drowned in a deep despair. Indonesiaâ€™s multidimentional crisis had opened all the â€œmasksâ€, to its most hidden parts.This multidimensional crisis- in despair, emotionally, and sinically- had showed Indonesia as "a heap of delusions", no more nationalism, heroism, justice, unity, honesty, or proud. In conclusion, the old institusions survived with no dignityÂ This article focuses about Indonesia Nationalismâ€™s Chalange In the Globalization Era